Words and Works : Studies in Medieval English Language and Literature in Honour of Fred C. Robinson. - Baker, Peter S. (Toronto Old English Studies., 1998)
With contributions by some of the leading scholars in the field, this book is a distinguished collection of essays on Old and Middle English literature and textual analysis.